Test of the infrared wide-field camera OMEGA2000 and its application for an extragalactic survey - Kovács, Zoltán (2006)
OMEGA2000 is a prime-focus, near-infrared, wide-field camera, mounted on the 3. 5m telescope at Calar Alto. The camera uses a 2kx2k HAWAII-2 Focal plane array with a sensitivity from z to K band. In the first part of the thesis, we discuss the work aimed at optimizing the operation of the HAWAII-2 detector installed in the camera. We tested the operation of three speciemen from the HAWAII-2 family and compared their performances with each other. The MANOS Deep Field Survey, called COMBO-17+4 NIR, is planned to to extend the results of the COMBO-17 project to higher redshifts by using this camera. The currently available data restricted the original project to the COMBO-17+2 NIR survey. In the second part of the thesis we discuss the results produced by COMBO-17+2 NIR. We present the redshift distribution of bright infrared galaxies observed in the COMBO S11 field and analyse the evolution of their number counts for four galaxy types defined by their restframe colors. We find a decline in the number of the old elliptical and evolved spiral galaxies at z>1.5, whereas the actively star-forming galaxies become the dominating population at z>1. This is in a broad agreement with earlier results. For Extremely Red Objects (EROs) in the COMBO S11 field selected with R-H